The blocked completion of the European Monetary Union: Making the case for a pragmatic use of fiscal leeway - Daniel Seikel; Achim Truger (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2019)
The reform of the euro zone is stuck. Against the background of political blockades, this report examines from a combined economic and political science perspective how the Euro can be prepared for the next crisis. The report first identifies general requirements for the stabilization of economic and monetary union. Next, the report reconstructs the political logic of the euro crisis and shows that the prospects for realizing far-reaching reform proposals aiming at a fiscal union are poor. Subsequently, the report develops a proposal of how, under the given circumstances, the room for maneuver within the existing framework of economic and monetary union can be extended in a pragmatic way in order to strengthen national fiscal policy as an instrument of macroeconomic stabilization.
urn:nbn:de:101:1-2019102415541542958169
Keywords: 330